2018
DOI: 10.1149/2.0311809jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic and Electroanalytic Investigation of Carbohydrates Oxidation on Gold-Based Nanocatalysts in Alkaline and Neutral pHs

Abstract: The design and fabrication of durable nanocatalysts to efficiently and selectively electro-oxidize organic molecules toward valueadded product(s) is an important starting point for the future deployment of electrochemical "cogeneration" devices with the triple advantage of producing electricity, heat and fuels/chemicals. This interdisciplinary research requires a synergistic effort from three communities of electrochemistry/electrocatalysis, material science and organic chemistry. To this end, we chose to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 78 publications
1
35
0
Order By: Relevance
“…Whilst this behavior seems counterintuitive according to Butler–Volmer kinetics, the complexity of the reactions taking place during the GA oxidation (see product analysis below) may lead to unexpected empirical observations. This behavior has been previously observed for ethanol oxidation on different electrocatalysts [53,61,62] and was associated with adsorption of ethanol to the electrode surface as the rate‐determining step and also for carbohydrates oxidation on gold electrodes, [63] although in the latter case a volcano‐shaped curve was obtained (i. e., initial increment of E a with the overpotential up to an inversion point where the E a starts decreasing with overpotential). It is worth noting that the complexity of the LA and GA oxidation reactions makes the interpretation of these values quite difficult and any quantitative conclusions are not definitive.…”
Section: Resultssupporting
confidence: 73%
“…Whilst this behavior seems counterintuitive according to Butler–Volmer kinetics, the complexity of the reactions taking place during the GA oxidation (see product analysis below) may lead to unexpected empirical observations. This behavior has been previously observed for ethanol oxidation on different electrocatalysts [53,61,62] and was associated with adsorption of ethanol to the electrode surface as the rate‐determining step and also for carbohydrates oxidation on gold electrodes, [63] although in the latter case a volcano‐shaped curve was obtained (i. e., initial increment of E a with the overpotential up to an inversion point where the E a starts decreasing with overpotential). It is worth noting that the complexity of the LA and GA oxidation reactions makes the interpretation of these values quite difficult and any quantitative conclusions are not definitive.…”
Section: Resultssupporting
confidence: 73%
“…Due to the scarcity and the high price of noble metals such as Pt and Au, pure metal electrodes are not easily scalable because high costs that are involved. In order to lower the amount of metal loading on the anode, whilst preserving the selectivity and the reactivity of the metal, Holade et al reported a selective electro-oxidation of glucose using Au nanoparticles on carbon as the anode material [ 73 , 74 ]. The aim of their work was to develop a highly efficient fuel cell which harvests electrical power from the oxidation of glucose, while producing added value chemicals.…”
Section: Electrochemical Oxidation Of Biomassmentioning
confidence: 99%
“…48,49 Interestingly for electrical energy consumption issues, oxidation reactions can be coupled with the hydrogen evolution reaction at the cathode. For example, by investigating cellulose's monomer and dimer selective electrolysis, 50,51 it opens the way to a possible development of electrolysers based on electrochemical interfaces that selectively oxidize cellulose (most abundant biopolymer, 35-50% of biomass) to produce organic molecules and H2. Indeed, given the low oxidation potential of those organics, their use lowers the input energy compared to water electrolysis (≥ 2-times).…”
Section: Introductionmentioning
confidence: 99%